Control of Attention in Rhesus Monkeys Measured Using a Flanker Task - Hassett, Thomas C.; Hampton, Robert R. (Attention, perception & psychophysics, 2022)
At least three processes determine whether information we encounter is attended to or ignored. First, attentional capture occurs when attention is drawn automatically by “bottom up” processes, to distinctive, salient, rewarding, or unexpected stimuli when they enter our sensory field. Second, “top down” attentional control can direct cognitive processing towards goal-relevant targets. Third, selection history, operates through repeated exposure to a stimulus, particularly when associated with reward. Attentional control is measured using tasks that require subjects to selectively attend to goal-relevant stimuli in the face of distractions. In the Eriksen flanker task, human participants report which direction a centrally placed arrow is facing, while ignoring “flanking” arrows that may point in the opposite direction. Attentional control is evident to the extent that performance reflects only the direction of the central arrow. We describe four experiments in which we systematically assessed attentional control in rhesus monkeys using a flanker task. In Experiment 1 , monkeys responded according to the identity of a central target, and accuracy and latency varied systematically with manipulations of flanking stimuli, validating our adaptation of the Eriksen flanker task. We then tested for converging evidence of attentional control across three experiments in which flanker performance was modulated by the distance separating targets from flankers (Experiment 2 ), luminance differences (Experiment 3 ), and differences in associative value (Experiment 4 ). The approach described is a new and reliable measure of attentional control in rhesus monkeys that can be applied to a wide range of situations with freely behaving animals.